2023
DOI: 10.20944/preprints202301.0528.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Therapeutic Properties of Polyphenols Affect AMPK Molecular Pathway in Hyperlipidemia

Abstract: Hyperlipidemia is the fat particles excess in the serum. Hyperlipidemia increases the mortality rate that occurs with other metabolic disorders. Hyperlipidemia is classified into familial and acquired subgroups. Moreover, Hyperlipidemia etiology is based on environmental or genetic factors. For instance, abnormal HMG-CoA regulation down-regulates ubiquitin ligase and targets variable oxidative stress-related condition proteins. There has been proven reactive oxygen species (ROS) overshoot happens during hyperl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 361 publications
0
2
0
Order By: Relevance
“…Studies have shown that polyphenolics can modulate the composition and function of gut microbiota, which can help to improve metabolic parameters [ 45 , 48 ]. In addition to their effects on gut microbiota, polyphenolics can also directly modulate metabolic processes in various organs such as the liver, adipose tissue, and skeletal muscle [ 45 , 48 , 49 ], and have been found to activate AMP-activated protein kinase (AMPK), which is a key regulator of energy metabolism [ 50 , 51 ]. Activation of AMPK can help to increase glucose uptake and utilization, reduce lipid accumulation, and improve insulin sensitivity [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that polyphenolics can modulate the composition and function of gut microbiota, which can help to improve metabolic parameters [ 45 , 48 ]. In addition to their effects on gut microbiota, polyphenolics can also directly modulate metabolic processes in various organs such as the liver, adipose tissue, and skeletal muscle [ 45 , 48 , 49 ], and have been found to activate AMP-activated protein kinase (AMPK), which is a key regulator of energy metabolism [ 50 , 51 ]. Activation of AMPK can help to increase glucose uptake and utilization, reduce lipid accumulation, and improve insulin sensitivity [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their effects on gut microbiota, polyphenolics can also directly modulate metabolic processes in various organs such as the liver, adipose tissue, and skeletal muscle [ 45 , 48 , 49 ], and have been found to activate AMP-activated protein kinase (AMPK), which is a key regulator of energy metabolism [ 50 , 51 ]. Activation of AMPK can help to increase glucose uptake and utilization, reduce lipid accumulation, and improve insulin sensitivity [ 51 , 52 ]. The bioavailability of polyphenolics is a crucial factor in determining their therapeutic potential.…”
Section: Discussionmentioning
confidence: 99%